Relationship between brain size and digestive tract length support the expensive-tissue hypothesis in Feirana quadranus - Fu, Yiping; Song, Yanling; Yang, Chao; Liu, Xinyi; Liu, Yenan; Huang, Yan (Frontiers in Ecology and Evolution, 2022)
The brain is among the most energetically costly organs in the vertebrate body, while the size of brains varies within species. The expensive-tissue hypothesis (ETH) predicts that increasing the size of another costly organ, such as the gut, should compensate for the cost of a small brain. Here, the ETH was tested by analyzing the relationship between brain size variation and digestive tract length in Swelled-vented frog (Feirana quadranus). A total of 125 individuals across 10 populations ranging from 586 m to 1702 m a.s.l. from Qinling-Daba Mountains were sampled. With the increase in altitude, the brain size decreases and the digestive tract length increases. Different brain regions do not change their relative size in a consistent manner. The sizes of optic tectum and cerebellum decrease with the increase in altitude, while the olfactory bulb increases its size at high altitudes. However, the olfactory nerve and telencephalon have no significant relationship with altitude. After controlling for snout-vent length (SVL), a significant negative correlation could be found between brain size and digestive tract length in F. quadranus. Therefore, the intraspecific variation of brain size follows the general patterns of ETH in this species. The results suggest that annual mean temperature and annual precipitation are environmental factors influencing the adaptive evolution of brain size and digestive tract length. This study also found a significant evolutionary relationship between brain volume and digestive tract length, thus providing a theoretical basis for subsequent studies on the evolutionary relationship between brain volume and the size of other organs.